Preparation, Structural Characterization and Biological Activities of Curcumin-Metal(II)-L-3,4-dihydroxyphenylalanin (L-dopa) complexes - Salh, Hala M.; Al-Noor, Taghreed H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In the present work, a first-row divalent d-transition metal obtained from curcumin(Curc)  and L-3,4-dihydroxyphenylalanin(L-dopa)have been synthesized which their complexes and characterized by  C.H.N, conductance, spectral methods: FT-IR, Ultra–Visible. Magneto-chemical measurements, molar conductance ΛM (1×10−3 mol/L in DMSO):36- 0.84 ohm-1.cm2.mol-1 (non-electrolyte).The data shows that the complexes have the structure [M((II))-(Curc)-(L-dopa)] system. Electronic and magnetic data suggest an octahedral geometry for all complexes in which the (L-dopa) and curcumin act as bidentate ligands.Curcumin coordinated to the metal ions M (II) through the lone pair of electrons of oxygen in 2(C=O) groups. The (L-dopa) coordinated to M (II) as a mono negative bidentate ligand through the oxygen atom of the carboxylate and the (N), atom of the (-NH2) groups.   The general formula  was given for the prepared mixed ligand complexes as [M (Cur)(L-dopa)2 ].  M= Mn  (II), Fe (II),Co(II),Ni(II),Cu (II), Zn(II), Cd(II) and Hg(II).The ligands and their metal complexes were screened for their antimicrobial activity klebsiella pneumonie,and  Staphylococcus aureus, and Candida albicans. Metal chelates showed very good antimicrobial activity than their parent curcumin-and (L- dopa).  We have given the general formula for the prepared mixed ligand complexes as [M (Cur)(L-dopa)2].M= Mn  (II), Fe (II),Co(II)  ,Ni(II),Cu (II), Zn(II), Cd(II) and Hg(II).The ligands and their metal complexes were screened for their antimicrobial activity klebsiella pneumonie,and  Staphylococcus aureus, and Candida albicans. Metal chelates show very good antimicrobial activity than their parent Curcumin-and (L- dopa).